Seasonal diet by a generalist raptor: the case of the variable hawk (Geranoaetus polyosoma) at Atacama Desert, northern Chile. Issue 2 (3rd April 2018) - Ponce, Cristóbal; Carevic, Felipe S.; Carmona, Erico R.
ABSTRACT: We determined the seasonal diet of the variable hawk, Geranoaetus polyosoma, in a hyperarid and threatened habitat in the Atacama Desert, northern Chile, by analysing the contents of the bird's pellets. We estimated the biomass and number of individuals of each prey species consumed. We compared our results with those of other studies on G. polyosoma in South America. In general, the diet was characterised by extremely low number of prey, low diversity of species consumed and high dietary breadth. In contrast with other biomes of Chile, in our study reptiles formed the dominant food item and accounted for the highest percentage of biomass consumed from autumn to spring, with rodents being a seasonally significant major food item. Arthropods were also consumed, but the biomass ingested was negligible. Statistically significant differences were noted across seasons in the prey items consumed, reflecting a flexible and opportunistic response to the scarcity of prey available. Our findings add to the data present on the basic natural history of G. polyosoma and can aid in its conservation in the Atacama Desert.